THE SIGNIFICANCE OF PROGNOSTIC PROFILING IN THE TREATMENT OF PATIENTS WITH MULTIPLE MYELOMA - Mitrovic, Marko; Sretenović, Aleksandra; Bila, Jelena (Medicinski podmladak, 2020)
Multiple myeloma (MM) is a hematological neoplasia characterized by clonal expansion of the most mature B lymphocytes, plasma cells (Plc), in the bone marrow (BM). Due to new treatment modalities, the 5-years survival has improved in the last 15 years, and nowdays ranges from 60-70%. The individual prognostic profile is based on the biological characteristics of the disease, clinical characteristics of patients and therapeutics response characteristics. The biological characteristics of the disease are defined by the clinical stage according to the Durie-Salmon classification and prognostic indices such the international staging system (ISS) and revised ISS (R-ISS). Numerous different mutations of prognostic significance have been discovered applying methods of molecular genetics such as next generation sequencing (NGS). The age and comorbity status of patients are the most important clinical characteristics because they are crucial for therapeutic choice and suitability for treatment with high-dose chemotherapy and autologous stem cell transplantation. The prognostic influence of therapeutic response is very important and the most powerful prognostic factors are achievements of complete remission (CR) and minimal residual disease (MRD) negativity.